Security box by using membrane keypad / Mohammad Nurul Akmal Safe’i, Mohammad Safwan Mohamad Kuturi and Muhammad Anuar Zainal Abidin - Safe’i, Mohammad Nurul Akmal; Mohamad Kuturi, Mohammad Safwan; Zainal Abidin, Muhammad Anuar (2015)
The main purpose of this project is to design a security box membrane keypad as an input to open the box. Ordinary box usually need an addition lock to make the box in safe condition. However, at the same time it makes the user hard to handle that kind of box because they need to use and keep too many keys based on the number of the lock. The keys may have a possibility to loss if it does not keep carefully. To handle this problem, this security box is design to help people keep their important files or things in the box without using any keys. To open the box, the user has to switch on first the circuit using multi switch as a security option. Then insert the password on the membrane keypad. If switch successfully connect to the circuit followed by the pin on membrane keypad, the box is open and user able to keep their important files and things in the box.